PENGARUH CONTENT MARKETING, ONLINE CUSTOMER REVIEW DAN LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen TikTok Shop Mahasiswa Universitas Budi Luhur) - Fita Nur Hanifah; Ravindra Safitra Hidayat (CV. Denasya Smart Publisher, 2024)
The research was conducted with the aim of explaining how digital marketing factors influence consumer purchasing decisions on the TikTok Shop platform. The main objective of this study is to evaluate the effect of content marketing, online customer reviews and live streaming on purchasing decisions for TikTok Shop among Budi Luhur University students. The research method used is a descriptive quantitative approach. The population of this study consisted of 2,030 active students of Budi Luhur University class of 2020. The sample of this study consisted of 100 respondents selected using probalibity sampling and purposive sampling techniques. The results showed that the variables of content marketing, online customer reviews and live streaming had a positive and significant effect on purchasing decisions at TikTok Shop in the Budi Luhur University student group.